Analisis Rekonstruksi Makna dan Kekuasaan dalam Pidato Rocky Gerung pada Kanal MimbarTube - Ghozali Bayu Eka Samudra; Roziana Febrianita (Yayasan Perguruan Kampus, 2024)
The Job Creation Law has become a controversial topic and has given rise to various problems in society. Political and social dynamics continue to change, speeches from public figures are important because they can influence public opinion, shape perceptions, and mobilize the masses. One figure who is known for raising socio-political issues with a provocative perspective is Rocky Gerung. The aim of this research is to analyze the reconstruction of meaning and power in the context of workers' struggles in Rocky Gerung's speech which was broadcast via the MimbarTube channel